2017
DOI: 10.1080/23744235.2017.1285045
|View full text |Cite
|
Sign up to set email alerts
|

Screening for early-onset invasive group B Streptococcal disease in neonates in an Irish hospital (2001–2014): a retrospective audit

Abstract: Group B Streptococcus (GBS) is the most common cause of early-onset neonatal sepsis and meningitis. In babies with no clinical suspicion of infection, who are at risk of early-onset invasive disease based on maternal risk factors, blood cultures are taken to detect bacteraemia. In our institution, lumbar punctures are performed in infants with clinical signs of sepsis but not in infants who are well at the time of screening. Between 2001 and 2014, there were 112,361 live births weighing >500 g, of whom 13,959 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Comparative studies within this field are limited by different and relatively short study periods, varying study populations, and different culture types [ 2 , 11 , 12 , 15 ]. While we only included term infants, several studies included preterm or extreme preterm infants [ 11 , 20 , 21 ], which may explain the predominance of Gram-negative rods previously reported [ 12 ]. Consistent with our findings, a recent study by Singh et al reported GBS to be the most prevalent cause of EOS in term infants admitted to the NICU, accounting for 62% of cases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies within this field are limited by different and relatively short study periods, varying study populations, and different culture types [ 2 , 11 , 12 , 15 ]. While we only included term infants, several studies included preterm or extreme preterm infants [ 11 , 20 , 21 ], which may explain the predominance of Gram-negative rods previously reported [ 12 ]. Consistent with our findings, a recent study by Singh et al reported GBS to be the most prevalent cause of EOS in term infants admitted to the NICU, accounting for 62% of cases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the severe situation of drug resistance, GBS infection is bound to become a substantial risk to the obstetric diseases associated to pregnant women and newborn children [16]. Additionally, there were significant differences in drug resistance, molecular and serotype of GBS between diseases categories, specimen types or regions [17,18]. MLST of GBS isolates from different countries indicated that only limited numbers including ST1, ST10, ST17, ST19 and ST23 were associated with colonizing or invasive isolates [19].…”
Section: Introductionmentioning
confidence: 99%